The Utility of ADCC Responses in HIV Infection - Chung, Amy; Rollman, Erik; Johansson, Susanne; Kent, Stephen J.; Stratov, Ivan (Current HIV Research, 2008)
Simple antibodies or vector-induced T cell immunity are unable to provide broad immunity to HIV. Although broadly reactive neutralising antibodies are a goal of vaccination, this remains elusive. There is growing evidence that HIV-specific antibodies that mediate their activity via the Fc-receptor, such as antibody dependent cellular cytotoxicity (ADCC), have an important role in controlling HIV infection. Newer assays are being developed that enable HIV-specific ADCC responses to be finely mapped. In turn, this should allow a more definitive analysis of the effectiveness of HIVspecific ADCC antibodies. However, progressive dysfunction of effector cells that mediate ADCC responses, such as NK cells, combined with immune escape variants that emerge from effective ADCC responses, likely undermine the utility of ADCC responses during chronic HIV infection. Nonetheless the utility of ADCC responses in preventing HIV infection requires urgent consideration.
Keywords: antibodies